2023
DOI: 10.1021/acsanm.2c05107
|View full text |Cite
|
Sign up to set email alerts
|

N,S-Codoped Carbon Nanostructures Encapsulated with FeNi Nanoparticles as a Bifunctional Electrocatalyst for Rechargeable Zn–Air Batteries

Abstract: The exploration of highly efficient, low-cost, and durable oxygen reduction reaction (ORR)/oxygen evolution reaction (OER) bifunctional electrocatalysts is extremely desirable but challenging for the practical application of Zn–air batteries. Herein, we report the fabrication of a FeNi alloy nanoparticle (NP)-decorated N,S dual-doped carbon nanocomposite (denoted FeNi/NS-C) as a bifunctional electrocatalyst for Zn–air batteries. The FeNi/NS-C electrocatalyst is produced through the complexation of a N-rich imi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The specific capacity was normalized to the mass of the consumed zinc plate for LIG-PtCoO x -1 and commercial 3.39 wt % Pt/C. The specific capacity was 739 mA h/g Zn at a discharging current of 20 mA/cm 2 , exceeding that of the commercial Pt/C battery (specific capacity = 605 mA h/g zn ) compared with the theoretical specific capacity (820 mA h/g Zn ), 20 wt % Pt/C and IrO 2 -based Zn–air batteries (761 mA h/g Zn ), and a majority of the published Pt-based electrocatalysts. , Further discharge stability tests show that LIG-PtCoO x -1 maintains a constant voltage output of 1.03 V at 20 mA/cm 2 , which only decreases 63.4 mV in 9 h (Figure S14b). These results demonstrate that optimization of both mass transfer and charge transfer through the PtCoO x configuration in LIG-PtCoO x -1 as very essential for application in practical electrochemical energy storage devices.…”
Section: Resultsmentioning
confidence: 97%
“…The specific capacity was normalized to the mass of the consumed zinc plate for LIG-PtCoO x -1 and commercial 3.39 wt % Pt/C. The specific capacity was 739 mA h/g Zn at a discharging current of 20 mA/cm 2 , exceeding that of the commercial Pt/C battery (specific capacity = 605 mA h/g zn ) compared with the theoretical specific capacity (820 mA h/g Zn ), 20 wt % Pt/C and IrO 2 -based Zn–air batteries (761 mA h/g Zn ), and a majority of the published Pt-based electrocatalysts. , Further discharge stability tests show that LIG-PtCoO x -1 maintains a constant voltage output of 1.03 V at 20 mA/cm 2 , which only decreases 63.4 mV in 9 h (Figure S14b). These results demonstrate that optimization of both mass transfer and charge transfer through the PtCoO x configuration in LIG-PtCoO x -1 as very essential for application in practical electrochemical energy storage devices.…”
Section: Resultsmentioning
confidence: 97%
“…PA@Z8-Fe-N-C 0.89 1.77 0.89 Gao et al [ 78] Fe/Fe-NC-3 0.87 1.69 0.82 Deng et al [ 91] Co/N-Pg 0.82 1.63 0.81 Tian et al [ 92] Fe-ZIF/OCNT 0.865 1.672 0.807 Sheng et al [ 93] FeCo-N-C 0.81 1.61 0.80 Wu et al [ 94] Co@N-C 0.82 1.58 0.76 Ma et al [ 95] FeNi/NS-C 0.83 1.585 0.755 Li et al [ 96] Mn@Co-NS 0.89 1.61 0.72 Li et al [ 97] FeCo/N-CNT 0.87 1.58 0.71 He et al [ 98] CoNi@CoCN 0.86 1.57 0.71 Zhang et al [ 99] Co/CoFe@NC 0.84 1.54 0.70 Niu et al [ 100] interact with the electrons of sp 2 -C materials through the electron coupling effect, resulting in an activation effect. [86] In the M-N-C catalysts, the N atoms have lone electron pairs, which can form strong interactions with the metal atoms and facilitate the immobilization of metal atom dopants in the carbon skeleton.…”
Section: Group Imentioning
confidence: 99%
“…[127,128] Li et al reported a simple strategy to fabricate nitrogen, sulfur, and dual metal (Fe/Ni) co-doped carbon nanocomposite as an effective bifunctional catalyst for RZABs. [96] First, 1,4-bis(1-hexy-1Himidazo-[4,5-f ] [1,10] phenanthroline-2-yl) benzene (HIPB) compounds were synthesized and used as organic ligands to generate TM-mediated imidazole-o-phenanthroline derivatives (labeled as HIPB-M). HIPB-M was mixed with trithiocyanuric acid (TTCA) and pyrolyzed at a high temperature to obtain FeNi/NS-C electrocatalyst.…”
Section: Co-n-c Smcs With δE Between 07 and 09 Vmentioning
confidence: 99%
See 1 more Smart Citation
“…ZAB has drawn the attraction of researchers as one of the potential energy storage and conversion technologies. The two variables that have the greatest influence on ZAB performance are the characteristics of ORR and OER. However, the commercial growth and application of ZAB are constrained by the slow kinetics of the ORR and OER. The general trend to address this problem is to create a bifunctional oxygen electro-catalyst to catalyze ORR and OER. …”
Section: Introductionmentioning
confidence: 99%